2018
DOI: 10.1103/physreve.98.052903
|View full text |Cite
|
Sign up to set email alerts
|

Ploughing friction on wet and dry sand

Abstract: The friction for sliding objects over partially water-saturated granular materials is investigated as a function of the water volume fraction. We find that ploughing friction is the main sliding mechanism: The slider leaves a deep trace in the sand after its passage. In line with previous research and everyday experience, we find that the friction force varies nonmonotonically with the water volume fraction. The addition of a small amount of water makes the friction force sharply drop, whereas too much added w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…In spite of the relatively large attention the paper by Fall et al has attracted, it has remained without a quantitative explanation so far. Liefferink et al showed recently that the penetration hardness is related to the shear modulus, making the plausible argument that this related the friction with the modulus [15]. However quantitatively, this remained to be demonstrated, and that is exactly what we do here.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…In spite of the relatively large attention the paper by Fall et al has attracted, it has remained without a quantitative explanation so far. Liefferink et al showed recently that the penetration hardness is related to the shear modulus, making the plausible argument that this related the friction with the modulus [15]. However quantitatively, this remained to be demonstrated, and that is exactly what we do here.…”
Section: Introductionsupporting
confidence: 78%
“…The observed linear dependence of the friction coefficient on the hardness is a result of the geometry, in this case a flat slider over a flat sand-surface. Recently, for a sphere-on-flat geometry a quantitative relation is found where the the friction coefficient depends on the penetration hardness as μ ∼ P −1∕2 h [15]. Due to the simple geometry, the relevant contact areas in the normal-and tangential direction can be calculated based on the measured ploughing track which, in the end, controls the friction coefficient for sliding.…”
Section: Penetration Hardness P H (Kpa) (-)mentioning
confidence: 99%
“…The strong drop in the effective modulus with increasing strain amplitude of filled rubber compounds is also observed for other particle systems. Thus, the effective shear modulus of (slightly) wet sand as a function of the strain amplitude is very similar to that of the filled rubber compounds [23,24]; see Figure 11. For slightly wet sand, water capillary bridges bind the sand grains together.…”
Section: Discussionmentioning
confidence: 58%
“…This theory is based on Edwards statistical mechanics for jammed granular matter, see Ref. [24]. One difference is that for a granular material, such as sand, the thermal motion of the particles can be neglected, while the filler particles in rubber can be very small (of nanometer size) and in this case thermal motion cannot be neglected.…”
Section: Discussionmentioning
confidence: 99%
“…Adding a small amount of a wetting liquid to the particles allows the formation of capillary bridges between particles [1][2][3][4][5][6][7]. These bridges add tensile forces to the packing, resulting in a significantly increased mechanical stability [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]: it is simple to build vertical sand castle walls from wet sand while the same material in its dry state can not form piles with steeper slopes than its angle of repose around 30 • , which is dependent on the friction coefficient of the sand.…”
Section: Introductionmentioning
confidence: 99%